Designing Intelligent Variable Structure Controller for HIV Infection - Reza Ghasemi (Institute of Advanced Engineering and Science, 2013)
Fuzzy adaptive controller is developed for HIV infection in which functions of the system are unknown. A non-affine nonlinear system is considered for the HIV infection dynamic model. The merits of the proposed method is as the stability of the closed-loop system (HIV + Controller), the convergence of the infected cells concentration rates to zero and the boundedness of the internal signal and infected cell concentration. The simulation results show the promising performance of the proposed method.DOI: http://dx.doi.org/10.11591/ij-ai.v2i2.2024